The Optimum Dispersion of Carbon Nanotubes for Epoxy Nanocomposites: Evolution of the Particle Size Distribution by Ultrasonic Treatment - Tomas Roll Frømyr; Finn Knut Hansen; Torbjørn Olsen (Journal of Nanotechnology)
The ultrasonic dispersion of multiwalled carbon nanotube (MWCNT) suspensions was assessed by studying the differential sedimentation of the particles in an acid anhydride often employed as a curing agent for epoxy resins. The particle size distributions were characterized by the means of a disc centrifuge, and the effect of dispersion time, power density, and total energy input, for both bath and circulation probe ultrasonic dispersing equipment was investigated. The mass of freely suspended MWCNTs relative to agglomerated MWCNTs was estimated as a measure of the quality of the dispersions, and the results showed that this ratio followed a power law scaling with the energy dissipated in the sonication treatment. If the sonication power level was too high, sonochemical degradation of the curing agent could occur. The mean agglomerate MWCNT size distribution was estimated, and the fragmentation of the agglomerates was modeled by means of fragmentation theory. Indications of both rupture and erosion fragmentation processes for the MWCNT agglomerates were observed.